Activities of Lactation Management Centre of Rajshahi (TAJ: Journal of Teachers Association, 2009)
A total of 500 patients were attended at LMC of RMCH from July 2004 to June, 2005. Most of the mothers were not aware of breast feeding regarding attachment and position. About 95% of the mothers were trained about correct technique of breast feeding. 55% of mothers were in the age group. 15-20 Yrs. Oketani breast massage was given on an average of about 33% of mothers. Only 12% of attending mothers were suffered from different types of breast problems like-engorged breast, sore nipple, flat nipple, crack nipple and breast abscess.   doi: 10.3329/taj.v18i2.3173 TAJ 2005; 18(2): 89-92